Seasonal Variation of Fish Catches and Fisherman Practices for Sustainable Fishery Management in Songkhla Lake, Thailand - Ha Thi Thu Hue (Prince of Songkla University, 2024)
Doctor of Philosophy (Marine and Coastal Resources Management), 2019